1984
DOI: 10.1288/00005537-198407000-00018
|View full text |Cite
|
Sign up to set email alerts
|

A simple operation for bilateral vocal cord paralysis

Abstract: To reduce the laryngeal obstruction in bilateral vocal cord paralysis, a new method of laterofixation was developed. The method is technically simple and less traumatic than previously published methods. No peroperative tracheostomy is needed. During surgery two needles are inserted through the thyroid cartilage. A nylon thread is passed through the needles and the needles are then withdrawn. The thread thus forms a permanent loop around the vocal cord. The effects of the laterofixation on breathing and on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
1
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(67 citation statements)
references
References 14 publications
0
60
1
5
Order By: Relevance
“…Voice impairment also occurred in all patients of this study; however, postoperative voice function was acceptable in all patients. Aspiration is described after laterofixation in some studies (13)(14)(15) but not in others (16)(17)(18) and was not experienced in the patient cohort analyzed here.…”
Section: Discussionmentioning
confidence: 72%
“…Voice impairment also occurred in all patients of this study; however, postoperative voice function was acceptable in all patients. Aspiration is described after laterofixation in some studies (13)(14)(15) but not in others (16)(17)(18) and was not experienced in the patient cohort analyzed here.…”
Section: Discussionmentioning
confidence: 72%
“…Kelly modified King's technique by excising the arytenoid through a window in the thyroid cartilage and by placing a suture to lateralize the vocal fold. [12] Ejnell et al [13] reported a new surgical technique for BVFI in 1984. Their method used laterofixation of the vocal fold, with a thread looped around the fold.…”
Section: Discussionmentioning
confidence: 99%
“…Only the patients with severe bilateral vocal cord immobility require surgical intervention. 4 The treatment of bilateral immobile vocal cords is a balance between phonation, airway, and swallowing. A wide range of techniques are nowadays used to enable the patient both to speak and to breathe without the need of permanent tracheostomy.…”
Section: Introductionmentioning
confidence: 99%